The Rule of Law as Political Philosophy - Dahal, Gopal Prasad (NUTA Journal, 2018)
In social science, rule of law indicates one of the most subjective and value loaded concepts. From the pragmatic vantage point, rule of law represents procedural device. This paper thus tried to appraise rule of law from philosophical perspectives. Based on literature review, my appraisal highlights that rule of law lays down under fundamental requirements for law by which those with power rule under the law. And for the citizen, the rule of law is both prescriptive (i.e. dictating the conduct required by law) and protective (i.e. demanding that government acts according to law) of the citizens. The notion of the rule of law is dependent upon the political foundations of a state that tailored to the concept upon a nation’s economic resources. Here is why, rule of law must follow political philosophy or ancient/modern natural law thought that corresponded good and equitable. And the rule of law must not to be confused with democracy, justice, equality (before the law or otherwise), human rights of any kind or respect for persons or for the dignity of the citizens. However, critical philosopher claimed that rule of law neither says about how the law is to be made by tyrants for democratic majorities nor says about ensuring fundamental rights and social justice. They also blamed that the rule of law is an ideological device engaged by those with power to mask the reality of that power in society, and the correlative powerlessness of the mass citizens.